EDUKASI DAN PEMERIKSAAN SADARI PADA REMAJA PUTRI DI UPT SMP NEGERI 20 - GRESIK - Nourma Yunita; Luluk Yuliati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Young women, especially those who have experienced menstruation, are considered that the reproductive organs are mature and have developed. According to GLOBOCAN data, the International Agency for Research on Cancer (IARC) in 2012 found that breast cancer was cancer with the highest percentage of new cases, amounting to 43.3%, and the rate of deaths due to breast cancer was 12.9%. This community service is to detect breast cancer in teenagers as early as possible by breast self-examination (BSE), so teenage women advise to do it themselves before and after menstruation because they know their standard breast structure. Therefore, if there is a lump or any other normal thing, then they will immediately realize it and do consultations, especially in the elderly. This examination should begin periodically every month so that the lump can be found at an early stage and can quickly if a lump or other abnormality in the breast is exposed. The method used in the form of training demonstrations and simulations of breast self-examination movements. Participants consisted of 123 students, and all of them had menstruated. The results obtained from education and breast self-examination are good knowledge 4.07% of students, unified enough 82.93% of students, and less than 13% knowledge. It means that there are still many students who are knowledgeable enough about the importance of early breast self-examination in conducting early detection of breast cancer.